Investigating The Long-chain Polyunsaturated Fatty Acid Biosynthesis Of The Brachyura (Scylla Olivacea And Gecarcoidea Lalandii) Using Transcriptomic And Gene Characterization Approach - Ting, Seng Yeat (2021)
Mud crabs is rich in eicosapentaenoic acid (EPA) and docosahexanoic acid (DHA). Utilization of fish oil or trash fish in aquaculture is deemed unsustainable. Hence, vegetable oils (VO) are explored as an alternative to fish oil. VOs are devoid of LC-PUFA, therefore the ability of the animal to de novo synthesize essential fatty acid (EFA) from C18 precursor is important for sustainable aquaculture. Consequently, formulations of diets are impeded by lack of information on elongase (elovl) and desaturase (fads) gene, accumulation of FA in the tissue is often a reflection of dietary fatty acid profile. Therefore, to illustrate the LC-PUFA biosynthesis mechanism, two different crabs (Scylla olivacea and Gecarcoidea lalandii) from different habitats (marine and terrestrial) and with different dietary preference was studied. Results showed that S. olivacea have four elovl subfamilies (elovl1, elovl4, elovl6, and elovl7), Δ9 fads and Δ6-like fads, while G. lalandii have two elovl (elovl1 and elovl6), Δ9 fads, and Δ6-like fads. In both crabs, elovl6 can efficiently convert C18 PUFA, MUFA, and SFA to their subsequent product, with a high conversion rate from C18 to C20. In comparison, S. olivacea elovl4 can elongate C18-C22 PUFA, whereas, in G. lalandii, this function is taken up by elovl1. Intriguingly, S. olivacea elovl1 does not showed any activity towards the exogenous substrate, in comparison, G. lalandii elovl1 can elongate SFA to 26:0, in addition to their ability to elongate PUFA.